Penerapan Model Ontologi dalam Perkembangan Game Digital - I Komang Maheza Yudistia; I Gusti Ngurah Anom Cahyadi Putra (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
This research develops an ontology for interactive digital games using the Methontology methodology, which includes the stages of specification, knowledge acquisition, conceptualization, integration, implementation, and evaluation. The development process involved using the Protégé tool to build and manage the ontology. The result is an ontology consisting of 32 classes, 12 property objects, 0 property data. This ontology was tested using SPARQL queries on the Jena Fuseki web, demonstrating its ability to support more effective classification and knowledge management. The application of this ontology improves data interoperability and the gaming experience and enables the development of more structured and complex applications. This research confirms the benefits of ontologies in enriching data structure and integration in the interactive digital game domain.